First-Principles Calculations of the Exchange Interaction of the CrGeTe3/NiO Interface - Liu, Xuehua; Li, Zhaoyuan; Zhang, Whenli; Yao, Pei; Zhu, Haoran; Liu, Xin; Zuo, Xu (Frontiers in Materials, 2022)
Two-dimensional (2D) magnetic materials have recently attracted a great attention due to their potential applications in information processing and storage. It was observed in an experiment that the CrGeTe3/NiO heterostructure shows a higher Curie temperature and a stronger perpendicular anisotropy. This suggests that antiferromagnet NiO can be coupled with ferromagnetic CrGeTe3 by the proximity effect, which enhances ferromagnetism. However, the mechanism behind the coupling is unknown. In this work, we built a CrGeTe3/NiO heterostructure model and investigated the electronic structure and magnetic properties of the CrGeTe3/NiO interface by first-principles calculations. It is shown that the intralayer exchange interaction between the Cr atoms is ferromagnetic, and the interlayer exchange interaction between the Ni atoms and Cr atoms at the interface is antiferromagnetic. The interlayer interaction is equivalent to a magnetic field as strong as B=100.3 T applied by the NiO substrate to the CrGeTe3 layer, which results in the higher Curie temperature of CrGeTe3 observed in the experiment.